PERUMUSAN STRATEGI PEMASARAN PRODUK MINUMAN BOBA “MIXUE” DENGAN MENGGUNAKAN MATRIKS INTERNAL EKSTERNAL - Ni Luh Gede Sari Marta Kyana; A. A. Ayu Tirtamara; Ni Nyoman Kerti Yasa (Jurnal Pijar, 2023)
The purpose of this research is to find out an attractive marketing strategy for Mixue Boba Drink in facing very tight competition. The approach used in this research is the SWOT Analysis and Internal-External Matrix. SWOT analysis is used to identify external factors (opportunities and threats) and internal factors (strengths and weaknesses). The results of the study based on internal external matrix analysis, it can be identified that the Raya Dalung "Mixue" Boba Drink, Badung, Bali, it is known that the Raya Dalung Mixue outlet is in quadrant II or in the "grow and build" position. In these conditions, the appropriate strategy to use is an intensive strategy and an integrative strategy. Intensive strategy includes market penetration and market development. The integration strategy includes backward integration, forward integration and horizontal integration. The market penetration strategy is a strategy to increase the current market share through increased marketing efforts.